One Pot Synthesis of γ-Iminolactones by Three Component Reactions Between Alkyl Isocyanides, Acetylenic Esters and Benzyl Phenyl Ketone and its α-Chloro Derivative - Asghari, S.; Ramezani, S.; Darvishnia, P. (Asian Journal of Chemistry, 2010)
The 1:1 intermediate generated by the addition of alkyl isocyanides to acetylenic esters is trapped by benzyl phenyl ketone and its derivatives to form γ-iminolactone derivatives.